Patterns of unemployment dynamics in Germany - Daniela Nordmeier; Enzo Weber (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2013)
This paper studies the patterns of unemployment dynamics in Germany. To provide a deeper insight into the margins of unemployment adjustment, we employ a structural VAR model and identify the effects of a technology shock as well as two policy shocks. We find that the worker reallocation process varies substantially with the identified shocks. The job finding rate plays a larger role following a technology shock and a monetary policy shock, while the separation rate appears as the dominant margin after a fiscal policy shock. Technology shocks are relatively important for variations in the transition rates, though they do not seem to trigger the high volatilities of German labor market variables. Considering policy shocks, our results point towards fiscal interventions as a promising instrument, but with several limitations. – – Die vorliegende Arbeit untersucht die Dynamik der Arbeitslosigkeit in Deutschland. Um einen tieferen Einblick in die Bestimmungsgründe der Schwankungen der Stromgrößen am Arbeitsmarkt zu gewinnen, verwenden wir ein strukturelles VAR-Modell und identifizieren die Effekte eines Technologieschocks sowie zweier Politikschocks. Unsere Ergebnisse zeigen, dass der Fluktuationsprozess mit den identifizierten Schocks variiert. Infolge eines Technologieschocks und eines geldpolitischen Schocks spielt die Einstellungsrate eine größere Rolle, während die Entlassungsrate nach einem fiskalpolitischen Schock als dominanter Faktor fungiert. Technologieschocks sind relativ bedeutend für die Schwankungen der Übergangsraten, wenngleich sie nicht die Ursache der hohen Volatilität von deutschen Arbeitsmarktvariablen zu sein scheinen. Die Analyse von Politikschocks deutet auf fiskalische Interventionen als vielversprechendes Instrument hin, jedoch mit diversen Einschränkungen.
Keywords: J63; E24; E32; 330; Unemployment dynamics; transition rates; structural VAR; policy shocks